2022
DOI: 10.1029/2021ef002553
|View full text |Cite
|
Sign up to set email alerts
|

Human‐Climate Coupled Changes in Vegetation Community Complexity of China Since 1980s

Abstract: Vegetation community complexity is a critical factor influencing terrestrial ecosystem stability. China, the country leading the world in vegetation greening resulting from human activities, has experienced dramatic changes in vegetation community composition during the past 30 years. However, how China's vegetation community complexity varies spatially and temporally remains unclear. Here, we examined the spatial pattern of China's vegetation community complexity and its temporal changes from the 1980s to 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 79 publications
(127 reference statements)
1
7
0
Order By: Relevance
“…For example, the classification of planted forest types over various periods with the same vegetation map may present a challenge to our study because vegetation types have the potential to change. However, our previous studies have indicated that vegetation types in China are stable 23 , 24 , justifying our use of the same vegetation map to classify planted forest types across different periods. Recognizing that C density changes with forest age, we constructed a C density database based on the national forest inventory data, considering age-dependent C density variations (see Methods).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…For example, the classification of planted forest types over various periods with the same vegetation map may present a challenge to our study because vegetation types have the potential to change. However, our previous studies have indicated that vegetation types in China are stable 23 , 24 , justifying our use of the same vegetation map to classify planted forest types across different periods. Recognizing that C density changes with forest age, we constructed a C density database based on the national forest inventory data, considering age-dependent C density variations (see Methods).…”
Section: Discussionmentioning
confidence: 94%
“…For example, the classification of planted forest types over various periods with the same vegetation map may present a challenge to our study because vegetation types have the potential to change. However, our previous studies have indicated that vegetation types in China are stable 23,24 From 1990 to 2020, the increase in China's planted forests C storage due to area expansion exceeded 50% of the total C storage increment in China's planted forests (Figs. 2 and 3).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The purpose of segmentation is to divide a structure into multiple sets of neighboring points and to divide these points based on segmentation granularity through semantic segmentation (scene level), instance segmentation (target level), and partial segmentation (part level). Guo et al [4] discussed all available 3D point cloud semantic segmentation methods and divided these methods into projection-based, discretion-based, pointbased, and hybrid methods.…”
Section: A 3d Point Cloud Segmentationmentioning
confidence: 99%
“…The tropical and subtropical forest biomes of Southeast Asia are among the most imperiled regions of the planet's 36 biodiversity hotspots, with less than five percent of the natural ecosystems remaining intact (Buchadas et al., 2022; Hoang & Kanemoto, 2021; Pratzer et al., 2023; Su et al., 2022). Geographical shifts in species distribution have been observed (Early et al., 2016; Ruyn et al., 2014; Sunday et al., 2012), and it is expected that local species will accelerate their movement to higher elevations (Cazzolla Gatti et al., 2019; Elsen et al., 2021; Pecl et al., 2017).…”
Section: Introductionmentioning
confidence: 99%